Comprehensive analysis of potential cellular communication networks in advanced osteosarcoma using single-cell RNA sequencing data - Xu, Ning; Wang, Xiaojing; Wang, Lili; Song, Yuan; Zheng, Xianyou; Hu, Hai (Frontiers in Genetics, 2022)
Osteosarcoma (OS) is a common bone cancer in children and adolescents, and metastasis and recurrence are the major causes of poor treatment outcomes. A better understanding of the tumor microenvironment is required to develop an effective treatment for OS. In this paper, a single-cell RNA sequencing dataset was taken to a systematic genetic analysis, and potential signaling pathways linked with osteosarcoma development were explored. Our findings revealed 25 clusters across 11 osteosarcoma tissues, with 11 cell types including "Chondroblastic cells", "Osteoblastic cells", "Myeloid cells", "Pericytes”, “Fibroblasts", "Proliferating osteoblastic cells", "Osteoclasts", "TILs”, “Endothelial cells", "Mesenchymal stem cells", and "Myoblasts". The results of Cell communication analysis showed 17 potential cellular communication networks including “COLLAGEN signaling pathway network”, “CD99 signaling pathway network”, “PTN signaling pathway network”, “MIF signaling pathway network”, “SPP1 signaling pathway network”, “FN1 signaling pathway network”, “LAMININ signaling pathway network”, “FGF signaling pathway network”, “VEGF signaling pathway network”, “GALECTIN signaling pathway network”, “PERIOSTIN signaling pathway network”, “VISFATIN signaling pathway network”, “ITGB2 signaling pathway network”, “NOTCH signaling pathway network”, “IGF signaling pathway network”, “VWF signaling pathway network”, “PDGF signaling pathway network”. This research may provide novel insights into the pathophysiology of OS's molecular processes.